A Multidisciplinary Approach to the Development of Thermal Clay Modules - Flemming Tvede Hansen; Isak Worre Foged; Vasiliki Fragkia (FORMakademisk, 2023)
This study focuses on the idea that industrial production methods, combined with a craft-based approach, enable the production of distinctive expressive thermal functionalities. We developed extruded modules based on a hands-on explorative craft approach in parallel with virtual simulations to explore how heat and cold are transported dynamically through building modules. This paper discusses the developed method and process used in a multidisciplinary approach that combines the quality of craft-based practice with architecture, engineering and programming, focusing on how craft practitioners experiment with material, technique and aesthetics in such a multidisciplinary approach. In this study, immediate concrete design proposals demonstrated a helpful way of establishing common ground for multidisciplinary collaboration. Concrete design proposals are pivotal in addressing the suggested design’s advantages and disadvantages and clarifying the differences and potentials between the specialisations in question. Based on the initial design proposals, it was clear how the craftsperson’s previous experiences within crafts practice quickly led to the identification of realisable solutions based on experimental setups and aesthetic solutions and, at the same time, was able to foresee possible complications.